Novel polyphosphazene-hydroxyapatite composites as biomaterials. - Laurencin, C.T (IEEE Engineering in medicine and biology magazine)
Evaluating a polymer-ceramic biomaterial as a candidate for bone tissue engineering. The objective of the present work was to develop novel composites of biodegradable polyphosphazenes and HA as candidate materials for bone tissue engineering. The mechanical and degradation properties of novel PPHOS/HA composites were compared to PLAGA/HA composites as PLAGA being the most extensively investigated polymer for bone tissue engineering application.